The Effect Of Land Use Conversion On Groundwater Quality In Dukuhwaluh Village Kembaran Subdistrict Banyumas Regency - Wiwit Sayekti Rahayu; Suwarsito Suwarsito; Esti Sarjanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Groundwater is the main source of water that is used to meet basic human needs. Thisstudy aims to determine the effect of land conversion on groundwater quality inDukuhwaluh Village, Kembaran District, Banyumas Regency. This study uses a surveymethod. The population in this study is groundwater. The sampling technique of thisresearch is purposive area sampling with the criteria of settlement density and distancebetween wells. Sampling was carried out at 6 sample points. The data used in this studyare primary data including land use data in 2020 and groundwater quality data.Secondary data includes data on area, land use, livelihoods, and education level. Primarydata collection through field observations in the form of land use collected for land use in2020 and groundwater quality data for temperature, pH, TDS parameters as well aslaboratory tests for ammonia, nitrate and e-colli bacteria parameters. Groundwaterquality analysis was carried out using the matching data method according to drinkingwater quality standards. The results showed that in the village of Dukuhwaluh there wasa conversion of an area of 14.235% of land into residential land. This can affect the qualityof groundwater in the presence of inappropriate ammonia and e-colli bacteria.